Cooperation between HMGA1 and HIF-1 Contributes to Hypoxia-Induced VEGF and Visfatin Gene Expression in 3T3-L1 Adipocytes - Messineo, Sebastiano; Laria, Anna Elisa; Arcidiacono, Biagio; Chiefari, Eusebio; Luque Huertas, Raúl M.; Foti, Daniela P.; Brunetti, Antonio (Frontiers in Endocrinology, 2016)
The architectural transcription factor high-mobility group AT-hook 1 (HMGA1) is a chromatin regulator with implications in several biological processes, including tumorigenesis, inflammation, and metabolism. Previous studies have indicated a role for this factor in promoting the early stages of adipogenesis, while inhibiting adipocyte terminal differentiation, and decreasing fat mass. It has been demonstrated that hypoxia – through the hypoxia inducible factor 1 (HIF-1) – plays a major role in triggering changes in the adipose tissue of the obese, leading to inhibition of adipocyte differentiation, adipose cell dysfunction, inflammation, insulin resistance and type 2 diabetes. To examine the possible cooperation between HMGA1 and HIF-1, herein, we investigated the role of HMGA1 in the regulation of Visfatin and VEGF, two genes normally expressed in adipose cells, which are both responsive to hypoxia. We demonstrated that HMGA1 enhanced Visfatin and VEGF gene expression in human embryonic kidney (HEK) 293 cells in hypoxic conditions, whereas HMGA1 knockdown in differentiated 3T3-L1 adipocytes reduced these effects. Reporter gene analysis showed that Visfatin and VEGF transcriptional activity was increased by the addition of either HMGA1 or HIF-1 and even further by the combination of both factors. As demonstrated by chromatin immunoprecipitation in intact cells, HMGA1 directly interacted with the VEGF gene and this interaction was enhanced in hypoxic conditions. Furthermore, as indicated by co-immunoprecipitation studies, HMGA1 and HIF-1 physically interacted with each other, supporting the notion that this association may corroborate a functional link between these factors. Therefore, our findings provide evidence for molecular cross-talk between HMGA1 and HIF-1, and this may be important for elucidating protein and gene networks relevant to obesity.